Genomic bacterial load associated with bacterial genotypes and clinical characteristics in patients with scrub typhus in Hainan Island, Southern China. - Gaoyu Wang; Ruijia Fu; Liyuan Zhang; Liying Xue; Abdullah Y Al-Mahdi; Xiaofei Xie; Aiping Qin; Chuanning Tang; Jiang Du; Yi Huang; Yueping Wang; Jian Su; et al. (Public Library of Science (PLoS), 2023)
Scrub typhus, caused by mite-borne Orientia tsutsugamushi (O. tsutsugamushi), is a major febrile disease in the Asia-Pacific region. The DNA load of O. tsutsugamushi in the blood was previously found to be significantly higher in patients with fatal disease than those with non-fatal disease and correlated with the duration of illness, presence of eschar, and hepatic enzyme levels. In this prospective observation study, we analyzed the association of bacterial DNA load with clinical features, disease severity, and genotype using real-time PCR targeting the 56 kDa TSA gene of O. tsutsugamushi in the blood samples of 117 surviving patients with scrub typhus who had not received appropriate antibiotic treatment. The median O. tsutsugamushi DNA load was 3.11×103 copies/mL (range, 44 to 3.3×106 copies/mL). The severity of patients was categorized as mild, moderate, and severe based on the number of dysfunctional organs, and no significant difference in O. tsutsugamushi DNA load was found among these groups. Patients infected with the Karp group showed a significantly higher O. tsutsugamushi DNA load than those in the Gilliam (P < 0.05) and TA763 (P < 0.01) groups. Patients belonging to the Li ethnic group showed a significantly higher DNA load than those in the Han ethnic groups. The blood bacterial DNA load of patients showed no significant difference between groups divided by gender, age, with or without eschar, or the season of disease onset. The highest body temperature recorded during fever onset was positively correlated with O. tsutsugamushi DNA load (ρ  =  0.272, P  =  0.022). Correlation analyses indicated that the serum total bilirubin level was positively correlated with O. tsutsugamushi DNA load. In conclusion, the findings in this study demonstrated the association of DNA load of O. tsutsugamushi with the severity and genotype in patients with scrub typhus in Hainan, China.